The theoretical and political pre-conditions of formation of the paradigm of political modernization - Хорішко, Л. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The preconditions of formation of the political modernization paradigm have been investigated. The theoretical pre-conditions (the acknowledgment of political system as a separate object of research, search of the subject, initiating the modernization processes and the optimal balance of traditional and current values during implementation of the reforms) facilitated the uprise of scientific discussions concerning the possible ways of modernization. The political pre-conditions (the establishment of national political systems, the increased level of society politicization, mass media development, legislative recognition of the fundamental rights and freedoms) made it actual for some certain systems to implement structural and substantial reforms for the sake of reaching the correspondent level of substantial development. The mentioned pre-conditions formed the backbone of formation of classical and advanced models of modernizational paradigm.